2016
DOI: 10.1007/s10940-016-9311-z
|View full text |Cite
|
Sign up to set email alerts
|

Violence in Urban Neighborhoods: A Longitudinal Study of Collective Efficacy and Violent Crime

Abstract: A longitudinal study of collective efficacy and violent crime 2 Biography John R. Hipp is a Professor in the departments of Criminology, Law and Society, and Sociology, at the University of California Irvine. His research interests focus on how neighborhoods change over time, how that change both affects and is affected by neighborhood crime, and the role networks and institutions play in that change. He approaches these questions using quantitative methods as well as social network analysis. He has published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 62 publications
4
50
0
Order By: Relevance
“…A particularly robust pattern detected was that cities with the lowest average income at the beginning of the decade experienced the sharpest increases in crime over the subsequent decade. These results are consistent with a broad swath of literature demonstrating the relationship between economic disadvantage and crime at various spatial scales (Hipp and Wickes 2016;Liska, Logan, and Bellair 1998;Sampson, Raudenbush, and Earls 1997;Weisburd, Groff, and Yang 2012), and our hypothesis 3. However, we also found that the economic health of the broader context impacted crime rate changes: cities located in counties with higher unemployment rates at the beginning of the decade, or counties that experienced unemployment increases during the decade, or counties experiencing increasing vacancy rates, suffered from increasing levels of almost all types of crime.…”
Section: Discussionsupporting
confidence: 92%
“…A particularly robust pattern detected was that cities with the lowest average income at the beginning of the decade experienced the sharpest increases in crime over the subsequent decade. These results are consistent with a broad swath of literature demonstrating the relationship between economic disadvantage and crime at various spatial scales (Hipp and Wickes 2016;Liska, Logan, and Bellair 1998;Sampson, Raudenbush, and Earls 1997;Weisburd, Groff, and Yang 2012), and our hypothesis 3. However, we also found that the economic health of the broader context impacted crime rate changes: cities located in counties with higher unemployment rates at the beginning of the decade, or counties that experienced unemployment increases during the decade, or counties experiencing increasing vacancy rates, suffered from increasing levels of almost all types of crime.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to the complicated relationship between neighborhood collective efficacy and other variables as acknowledged by recent research. For example, in a longitudinal study of the relationship between collective efficacy and neighborhood violence, Hipp and Wicks () did not find a direct relationship between the two variables, which is inconsistent with previous, cross‐sectional studies. Future research should explore variables that could potentially mediate the relationship between collective efficacy and collective action.…”
Section: Discussionmentioning
confidence: 70%
“…Recent research suggests that community members update their perceived neighborhood collective efficacy based on feedback and experiences within the community (Hipp, 2016). While longitudinal studies of collective efficacy are still limited, findings to date support the concept that perceived collective efficacy and overall neighborhood perceptions change over time (Hipp, 2016;Hipp & Wickes, 2018;Hipp & Wickes, 2016). Future research should apply longitudinal data to further analyze the potential mediating role of civic engagement in the relationship between collective efficacy and collective action.…”
Section: Limitationsmentioning
confidence: 98%
“…Neighborly interactions are influenced by structural characteristics that facilitate and impede opportunities for neighboring as well as by neighborhood social norms (Sampson, 2002). Consistent with research on antisocial behavior, neighborliness is higher in neighborhoods with less crime, less disadvantage, and higher levels of racial, ethnic, and socioeconomic homogeneity (Aiyer, Williams, Tolan, & Wilson, 2013;Brenner, Zimmerman, Bauermeister, & Caldwell, 2013;Hipp & Wickes, 2017;Tolan, Gorman-Smith, & Henry, 2003). Thus, neighborhood contexts shape social behavior.…”
mentioning
confidence: 81%